Depression, antidepressant use and mortality in later life: The health in men study - Almeida, O.; Alfonso, Helman; Hankey, G.; Flicker, L. (Public Library of Science, 2010)
Context: Depression is associated with increased mortality, but it is unclear if this relationship is dose-dependent and if it can be modified by treatment with antidepressants. Objective: To determine if (1) the association between depression and mortality is independent of other common potential causes of death in later life, (2) there is a dose-response relationship between increasing severity of depression and mortality rates, and (3) the use of antidepressant drugs reduces mortality rates. Methods: Cohort study of 5,276 community-dwelling men aged 68-88 years living in Perth, Australia. We used the Geriatric Depression Scale 15-items (GDS-15) to ascertain the presence and severity of depression. GDS-15=7 indicates the presence of clinically significant depression. Men were also grouped according to the severity of symptoms: "no symptoms" (GDS-15 = 0), "questionable" (1=GDS-15=4), "mild to moderate" (5=GDS-15=9), and "severe" (GDS-15=10). Participants listed all medications used regularly. We used the Western Australian Data Linkage System to monitor mortality. Results: There were 883 deaths between the study assessment and the 30th June 2008 (mean follow-up of participants: 6.0±1.1 years). The adjusted mortality hazard (MH) of men with clinically significant depression was 1.98 (95%CI = 1.61-2.43), and increased with the severity of symptoms: 1.39 (95%CI = 1.13-1.71) for questionable, 2.71 (95%CI = 2.13-3.46) for mild/moderate, and 3.32 (95%CI: 2.31-4.78) for severe depression. The use of antidepressants increased MH (HR = 1.31, 95%CI = 1.02-1.68). Compared with men who were not depressed and were not taking antidepressants, MH increased from 1.22 (95%CI = 0.91-1.63) for men with no depression who were using antidepressants to 1.85 (95%CI = 1.47-2.32) for participants who were depressed but were not using antidepressants, and 2.97 (95%CI = 1.94-4.54) for those who were depressed and were using antidepressants. All analyses were adjusted for age, educational attainment, migrant status, physical activity, smoking and alcohol use and the Charlson comorbidity index. Conclusions: The mortality associated with depression increases with the severity of depressive symptoms and is largely independent of comorbid conditions. The use of antidepressants does not reduce the mortality rates of older men with persistent symptoms of depression. © 2010 Almeida et al.